Modern Methods for Learning Outcomes Evaluation in Educational Institutions: Theoretical Investigation - Al-Zahrani, Huda Abdullah (Journal of Educational and Psychological Sciences, 2023)
The process of reviewing and evaluating postgraduate programs in educational institutions is one of the most important processes that have attracted the educational and academic researchers' attention in recent years (Falchikov, Boud 2015, Gilles 2007 & Detroz, & Blais 2011). Hence linking them to economic and social developments' plans and qualifying the educated for the labor market and meeting its needs. When we discuss assessment for learning, we must recognize that assessment strategies must aim to enhance student's learning (Sambell et al. 2013), support authoritative assessment (McDowell et al. 2011 & Sambell et al. 2013), students must be engaged in the learning process, not focus on grades (Sambell et al. 2013), learners should be given the opportunity to practice previously acquired skills or knowledge (Sambell et al. 2013), and feedback should combine written comments and discourse between the student, classmates, and teacher ( McDowell et al. 2011, Sambell et al. 2013), independent learners must also be developed (McDowell et al. 2011), that is what educational institutions seek today. All of these complicated issues around learning outcomes and their assessment seem to still be problematic in educational institutions. While learning was supposed to lead to the creation of an educated and aware generation, we find that educational institutions suffer from a decline in learning outcomes. Therefore, this article aims to provide a specific reference for teachers to benefit from and apply by discussing methods of evaluating learning outcomes to support the educational institutions' ability and raise the performance of courses and program's efficiency in order to achieve the desired goals sought by the ministry of education, and a theoretical presentation about: What can the concept of learning assessment include? What are the modern methods that have been proposed for learning evaluation? In addition to shedding light on some modern electronic and realistic assessment methods. The study concluded that: There is a significant deficit in defining the concept of learning assessment, with a focus on academic programs and courses. The study presented a set of recommendations, the most prominent of which are: the necessity of training in the use of modern evaluation methods and measuring the impact of training from the reality of educational institutions.
Keywords: Education Outcomes; Learning Assessment; Education; Methods; Educational Institutions